2009
DOI: 10.1111/j.1750-3841.2009.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Process of Black Soybean Natto Using Response Surface Methodology

Abstract: Response surface methodology (RSM) was used to determine the optimum combinations of 3 factors, cooking time (40 to 120 min), inoculated bacteria populations (10(1) to 10(9) cells/100 g), and fermentation time (12 to 36 h) for producing black soybean natto. All of the responses (hardness, viscosity, and trichloacetic acid-soluble nitrogen) were significantly affected by the 3 factors. Fermentation time was the most important factor affecting quality of black soybean natto. Optimum combinations were cooking tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Response surface methodology (RSM) can also be used to optimize a product formulation and process conditions (Chu & Resurreccion, 2005;Meullenet, Xiong, & Findlay, 2007;Shih, Yang, & Kuo, 2009). This is done by optimizing a response (dependent variable or output variable) by adjusting levels of independent variables (input variables) which are measurable, controllable and continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (RSM) can also be used to optimize a product formulation and process conditions (Chu & Resurreccion, 2005;Meullenet, Xiong, & Findlay, 2007;Shih, Yang, & Kuo, 2009). This is done by optimizing a response (dependent variable or output variable) by adjusting levels of independent variables (input variables) which are measurable, controllable and continuous.…”
Section: Introductionmentioning
confidence: 99%
“…2001). In our previous studies, we found that the viscosity was related to the proper growth of the microorganisms by decomposing the natto to produce the mucilage compounds with the enzymes (Shih et al . 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, black soybeans with green cotyledon were used for medicinal purposes as described in Ben Tsao Gong Mu, an ancient Chinese Botanical Encyclopedia, dating back to the early 16th century (Li 1990), or for making black soybean liquor. Black soybean had a higher antioxidative capacity than soybean (Shih et al . 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In product development and optimisation, response surface methodology (RSM) can be used to model and optimize any response affected by levels of one or more quantitative factors [7]. RSM has been widely applied for optimising processes in the food industry [8][9][10][11][12][13]. Hence the present study was aimed to extract the palmyra palm fruit pulp (PFP), process to decrease the bitter taste and to develop a ready to serve (RTS) beverage from PFP with optimized level of PFP and sugar.…”
Section: Introductionmentioning
confidence: 99%